CXCR4 blockade improves leukemia eradication by allogeneic lymphocyte infusion. Issue 6 (16th April 2018) - Jin, Chun‐Hui; Li, Yang; Xia, Jinxing; Li, Yuying; Chen, Mo; Hu, Zheng; Mapara, Markus Y.; Li, Wei; Yang, Yong‐Guang
Abstract: Persistent low levels of disease in bone marrow, an immunoprivileged tissue, are responsible for relapse following allogeneic hematopoietic cell transplantation. Using mouse models carrying primary human acute lymphoblast leukemia derived from MLL‐AF9‐overexpressing human hematopoietic stem cells, we demonstrate that allogeneic lymphocyte infusion (ALI)‐mediated graft‐vs.‐leukemia effects selectively spare leukemia cells in the bone marrow. The resistance of leukemia cells to ALI within bone marrow is due to the immunosuppressive status of the tissue, as ALI achieved a significantly increased complete remission rate when leukemia cells were dislodged from bone marrow by treatment with a CXCR4 antagonist AMD3100. Adoptive transfer experiments confirmed that the frequency of leukemia‐initiating cells in bone marrow was significantly decreased in the recipients treated with ALI plus AMD3100 compared to those receiving ALI only. These findings indicate that the immunoprivileged nature of bone marrow is largely responsible for relapse after immunotherapies, and that treatment with AMD3100 may offer a clinically‐practical approach to improving the outcome of adoptive allogeneic cell therapy.